Brand design and development "Nam Prik Mae Lek", a product of the Puranawat community enterprise, Thawi Watthana district, Bangkok - Phondee, Samran; Chesamae, Anhawi (Academic and Research Journal of Liberal Arts (Online), 2021)
This research aims to 1. Design and develop a brand “Nam Prik Mae Lek”, Puranawas Community Enterprise products that reflect local identity and add value to the product, 2. Study the level of consumer satisfaction with the brand "Nam Prik Mae Lek" Puranawas Community Enterprise products, Thawi Watthana District, Bangkok, that has been developed to lead development and production for sale. Which is a combination of research Both quality research and quantitative research. The research results were found that The distinctive identity of the Puranawas community is the cultural characteristics of the waterfront community. Surrounded by rich nature, people working in agriculture.There is a Puranawas temple. It’s the center of the community. The brand that has been designed and developed is "Nam Prik Mae Lek", an ancient recipe chili. It has a unique flavor that is recognized locally. With a contemporary design concept but still clearly retains the community identity Using graphics techniques. results of the quality assessment from experts found that The overall picture of the designed and developed brands was at a high level with a value = 4.44 and an SD = 0.67, while the evaluation of consumer satisfaction found that The overall picture is very high with values ​​= 4.45 and SD = 0.60 it was found that the issue of simplicity, beautiful, easy to remember the name of the product from the brand Received the highest score in a very good level (= 4.54 and SD = 0.57). The reflects that the brands that have been designed and developed are consistent with the new generation with low income. It is also contemporary, consistent with local identity and is of sufficient quality. Can be developed into the production process for sale to add value to the product further.